Numbers 3-10 are reminded and feminine - مهديّ موسى هاشم م. م (lark, 2020)
Arabic linguists’ viewpoints vary in stating how collective nouns are treated as masculine and feminine. While some linguists believe that treating collective nouns as masculine to indicate their large number, others tend to regard the stem of the utterance as masculine and its other utterances as feminine. Contemporary linguists examine the traditional linguists’ viewpoints; one group consider their views but the other group reject them. The study concludes that treating collective nouns as masculine and feminine respectively is due to the arbitrary use of Arabic language which often deviate from the standards set by linguists